Gladys Black letter to Nicholas S. Halmi regarding Snowy Owl count, February 1, 1977 - Black, Gladyset al (1977)
Report of Snowy Owl count contributed by Gladys Black in a letter to Nicholas S. Halmi. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter, 1976-1977. Epson - sheet feed/flatbed